Vortioxetine treatment for generalised anxiety disorder: a meta-analysis of anxiety, quality of life and safety outcomes. Issue 11 (28th November 2019) - Qin, Bin; Huang, Guangsu; Yang, Qian; Zhao, Mingjun; Chen, Hong; Gao, Wen; Yang, Mingxiu
Abstract : Objectives: The aim of this study was to investigate the efficacy, tolerability, safety, and impact on quality of life (QoL) and functional status of vortioxetine treatment for patients with generalised anxiety disorder (GAD) by performing a meta-analysis of randomised controlled trials (RCTs). Design: Systematic review and meta-analysis. Data sources: Data mining was conducted in January 2019 across PubMed, EMBASE, PsycINFO, Cochrane Central Register of Controlled Trials Cochrane Library, Web of science and ClinicalTrials.gov. Eligibility criteria for selecting studies: All published RCTs, which assessed the effect of vortioxetine treatment for patients with GAD when compared with a placebo group, were included. Data extraction and synthesis: Relevant data were extracted and synthesised narratively. Results were expressed as standardised mean differences or ORs with 95% CIs. Results: Our meta-analysis showed that multiple doses (2.5, 5 and 10 mg/day) of vortioxetine did not significantly improve the response rates, compared with placebo (OR 1.16, 95% CI 0.84 to 1.60, p=0.38; OR 1.41, 95% CI 0.82 to 2.41, p=0.21; and OR 1.05, 95% CI 0.76 to 1.46, p=0.75). Moreover, there was no statistically significant difference regarding the remission rates, discontinuation for any reason rates, discontinuation due to adverse events rates, Short-Form 36 Health Survey scores or Sheehan Disability Scale scores between administration of multiple doses (2.5, 5 and 10 mg/day) of vortioxetine and placebo. Conclusions: Although our results suggest that vortioxetine did not improve the GAD symptoms, QoL and functional status impairment of patients with GAD, it was safe and well tolerated. Clinicians should interpret and translate our data with caution, as the meta-analysis was based on a limited number of RCTs.